Pengaruh Likuiditas, Solvabilitas & Aktivitas terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderating (Studi Empiris Pada Perusahaan Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Ghaida Tyarna, Amira; Andy Dwi Bayu Bawono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to analyze the influence of liquidity, solvency, and activity on the value of a company as well as to find out whether profitability can moderate the liquidity of the company, and its activity on its value. This research uses quantitative methodology using secondary data. The sample used in this study included industrial companies that were listed on the Indonesian Stock Exchange in 2019-2022. The sampling techniques used are purposive samplings and as many as 37 companies have met the criteria as research samples. The analytical method used is double linear regression using SPSS version 26. The results show that liquidity and activity have no effect on the value of the company, while solvency has a positive effect on its value. Profitability does not moderate the relationship between liquidity and activity against the company's value, while profitability can moderate solvency against the value of the company.